How to measure the impact of place marketing activities: a methodological discussion. Issue 1 (2nd January 2020) - Rauhut, Daniel; Rauhut Kompaniets, Olga
ABSTRACT: This paper aims to explicate and discuss the main methods of measuring the effects of place marketing. Rather than favouring one method over another a priori, we seek to understand each method on its own terms in order to illuminate key assumptions and hypotheses. Additionally, we compare and contrast the different methods to reveal areas of logical inconsistency. Generally, the impact of place marketing activities is dominated by fragmented, often single case studies, analysed using qualitative methods. The methods hitherto developed to measure the effect of place marketing activities posit causal mechanisms in line with simple ex ante/ex post comparisons. As place marketing appears to be "political" and policy oriented, the need to understand what happens in the policy process and the context in which marketing activities take place is paramount, we need to unfold the political process so as to understand why and how some place marketing activities work, and others do not.